Supplementary Material Douglas-fir data [Conjunto de datos] - Cappa, Eduardo Pablo (2016)
Supplementary information of the three Douglas-fir trials, family numbers, and pedigree data including identity information of trees, fathers, and mothers of the paper entitled: Identification and joint modeling of competition effects and environmental heterogeneity in three Douglas-fir (Pseudotsuga menziesii var. menziesii) trials. Tree genetics & genomes 12 (6) : 102. (December 2016)